Experiences of Sexuality Education Educators in Secondary Schools of Mbarara Municipality, Uganda - Atuhaire, Judith; Nyakato, Viola N.; Murembe, Neema Clemencia (Eastern African Journal of Humanities and Social Sciences, 2024)
While schools in Uganda have sexuality education implementation programs in place, adolescents enrolled in school continue to have considerable concerns about sexuality. This indicates that there is still a gap in the teaching of sexuality education. Understanding, that the pursuit of excellent educational outcomes cannot understate the significance of educators. The objectives of the study were to understand how teachers have influenced the implementation of sexuality education in schools and to understand their influence. We explored their sexuality education teaching experiences. For this study, we purposively sampled 12 teachers from six secondary schools in Mbarara Municipality. These were classroom teachers teaching Biology, Christian Religious education and Literature, subjects in which topics about sexuality are included. Others were male and female senior teachers in charge of guidance and counselling; and teacher patrons to sexuality learning-related activities outside the classroom. Data was transcribed and analyzed through thematic coding of opinions, feelings, and practices of teachers. Results indicated that majority of teacher’s experience discomfort when teaching this subject. To most teachers, this discomfort was attributed to 1. Lack of proper training. 2. Others had strong cultural values and beliefs that made them uncomfortable teaching about sexuality in open places like the classroom. 3. Another minority, were not consulted before being appointed into counselling positions, therefore did not feel obliged to take on the assignment. 5. Lack of instruction materials. 6. Findings also revealed that students are not comfortable learning from their teachers, whom they consider as “second parents” and hence they join and learn more from peers and other adults. 7. While all students, learn about sexuality, only a few teachers are assigned this duty, this has created a teaching burden due to the low teacher-student ratio especially for duties like guidance and counselling and patronising of sexuality education programs. Thus, we deduced that SE was being jeopardised by teachers' inefficacy, attitude, and low teacher student ratio, and interaction of informal peer educators. We concluded that sexuality education educators, are most effective when they are equipped with skills, their consent to participate is sought, the education does not interfere with their values and when they do not carry an overload of assignments. From the findings, it was also evident that teachers are not the best choice schools should use to guide and counsel students about sexuality. Peers and medical personnel are preferred to teachers. Hence, when the identified gaps are attended to sexuality education will be more efficient to protect and keep skills with adolescents undergoing this education. To improve teacher performance, we recommend that schools assist their teachers in pursuing SE training, seek teachers consent before appointing them into SE educating or counselling positions, support them and offer teaching materials. The low teacher-to-student ratio be resolved by assigning more teacher educators SE roles. Our findings indicate that students feel more at ease studying with their peers than with teachers; hence, we recommended increasing the amount of supervised peer-to-peer SE learning in schools. We also discovered that students value media education, thus we recommend that schools offer more adult-guided media literacy instruction.
Keywords: Adolescents; Education; Educators; Sexuality